Comparative studies on efficacy of the Leishman-Giemsa stains, Hematoxylin-Eosin & Papanicolaou stains for cytological diagnosis of oral lesions - Dr Surajit Bose; Pof Dr Jayanta Chattopadhyay; Dr Maumita Bhattacharya; Dr Maumita Bhattacharya; Dr Sumantro Bandhopadhay; Dr Alangkar Saha; Pof Dr. Vertika Rai; Abhishek verma (The Bioscan, 2025)
Oral potentially malignant disorders are the precursors of oral cancers in India. Severealcoholism, use of tobacco like cigarettes, smokeless tobacco, betel nut chewing and humanpapilloma virus (HPV) are the most common risk factors for oral potentially disorder andmay also occur due to poor dental care and poor diet. The incidence of oral cancer is highest inIndia, South and Southeast Asian countries.Papanicolaou (PAP) stain is the routine and universal stain for the cytological procedure and iseasy and quick to perform for screening programs. The Leishman-Giemsa (LG) is an easy, cost–effective one-step technique. It needs less time and less infrastructural support. TheHematoxylin-Eosin stains are used routinely in Histopathological procedures. These newerstains like, LG are not much been utilized in oral exfoliative cytology. Hence, the present studywas designed to carry out the qualitative evaluation of cytological smears of patients with pre-malignant lesions using three different stains that are H&E, PAP, and LG. This is to ascertain theefficiency and reliability of these stains in evaluating cellular and nuclear atypia and correlatingthe cytopathological and histopathological grades